Improvement of soil available water capacity using biopore infiltration hole with compost in a coffee plantation - Atiqah Aulia Hanuf; Sugeng Prijono; S Soemarno (Journal of Degraded and Mining Lands Management, 2021)
Coffee plantation management has an important role in soil quality in order to increase coffee production. Biopore Infiltration Hole with Compost (BIHC) can increase soil available water capacity. In this study, the goal was to improve soil available water capacity in a coffee plantation with the implementation of the BIHC. This study was conducted at PTPN XII Bangelan, Malang, on March - August 2020. A randomized block design with seven treatments and four replications was used. The BIHC consisted of two-hole depths (30 cm and 60 cm) and two types of compost (goat manure and coffee pulp compost). The soil characteristics observed were water retention (pF) and C-organic at soil depths of 0-20, 20-40, and 40-60 cm. The coffee tree observed were number of leaves and chlorophyll content. Data obtained were subjected to analysis of variance (ANOVA) by the F test and Duncan's Multiple Distance Rate  Test (DMRT) at 5% probability, using SPSS program. Results of the study showed that BIHC was able to increase the content of soil C-organic and the available water capacity significantly compared with control treatment. The BIHC implementation could increase soil available water capacity up to 65% at a soil depth of 0-20 cm, up to 60% at a soil depth of 20-40 cm, and up to 51% at a soil depth of 40-60 cm more than the control treatment. The soil available water capacity suggested a significant positive correlation (p≤0.05) with the leaves number of coffee tree and chlorophyll content of leaves.